From Business Plan to Market Entry: A Case Study of Premium Bites Cookies in Malaysia’s F&B SME Sector - Samsudin, Zurina; Muhammad Sabri , Nur Hana Nazihah (JBS Nexus, 2025)
This paper explores the transformation of a home-based cookie initiative into a formal food startup, Premium Bites Cookies in Batu Pahat, Johor. The study examines key components of the startup’s business plan, including product–market fit, strategic positioning, and competitive advantage, while applying strategic frameworks such as SWOT, PESTEL, Porter’s Five Forces, and the Business Model Canvas. The findings reveal that structured business planning, niche market targeting, and the balanced integration of traditional and digital channels significantly enhance the scalability and resilience of early-stage SMEs in Malaysia’s competitive food and beverage (F&B) sector. The study contributes to SME and entrepreneurship literature by demonstrating how systematic planning and strategic alignment support sustainable market entry. Overall, this case offers practical insights for Malaysian SMEs by highlighting the importance of strategic clarity, digital capability development, and adaptive marketing approaches for achieving successful growth and long-term sustainability.